2014
DOI: 10.1177/0011000014535472
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Eating Among Asian/Asian American Women

Abstract: Sociocultural models of eating disorders emphasize the role of internalization of media standards of beauty in eating pathology but rarely examine (a) how racial and cultural factors may be related to women of color's tendency to endorse Western media beauty ideals or (b) these women's risk of developing body dissatisfaction and disordered eating issues. This study of Asian/Asian American women (N = 587) investigated the roles of perceived racial discrimination, ethnic identity, and racial/ethnic teasing in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 57 publications
3
24
0
Order By: Relevance
“…Given that racial discrimination makes phenotype-based stigma salient (Maddox, 2004), it is possible that reminders of racial discrimination may enhance any phenotypic actual-ideal discrepancies that might emerge for East Asians. Supporting this notion, perceived racial discrimination has been associated with Asians peoples' body dissatisfaction (Cheng, 2014;Iyer & Haslam, 2003;Reddy & Crowther, 2007), along with greater intentions in East Asians to undergo cosmetic procedures to remove phenotypic racial markers (Kaw, 1993). In turn, we propose that reminders of the direct antithesis of racial discriminationracial acceptancemay ameliorate such actualideal discrepancies in East Asians.…”
Section: Shifting the Actual-ideal Discrepancymentioning
confidence: 67%
See 2 more Smart Citations
“…Given that racial discrimination makes phenotype-based stigma salient (Maddox, 2004), it is possible that reminders of racial discrimination may enhance any phenotypic actual-ideal discrepancies that might emerge for East Asians. Supporting this notion, perceived racial discrimination has been associated with Asians peoples' body dissatisfaction (Cheng, 2014;Iyer & Haslam, 2003;Reddy & Crowther, 2007), along with greater intentions in East Asians to undergo cosmetic procedures to remove phenotypic racial markers (Kaw, 1993). In turn, we propose that reminders of the direct antithesis of racial discriminationracial acceptancemay ameliorate such actualideal discrepancies in East Asians.…”
Section: Shifting the Actual-ideal Discrepancymentioning
confidence: 67%
“…The present sample comprised both East Asian Americans and East Asians residing in the U.S. Past work has also collapsed these two groups together, arguing that the experiences EAST ASIAN ACTUAL-IDEAL DISCREPANCIES 16 of these groups in the U.S. cultural context are similar (e.g., Cheng, 2014;Chin Evans & McConnell, 2010;Hall, 1995;Frederick et al, 2016). Nevertheless, it would be important for future research in this area to collect larger samples of East Asian Americans and East Asians, to more accurately ascertain the the actual-ideal discrepancy for each of these groups separately.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%
See 1 more Smart Citation
“…For racial minorities, who possess phenotypic features that don't conform to this ideal, adherence to the White ideal can be damaging (Cheng, 2014;Iyer & Haslam, 2003;Reddy & Crowther, 2007). The present studies found evidence for an actual-ideal discrepancy in how racial minorities perceived themselves, phenotypically.…”
Section: Discussionmentioning
confidence: 44%
“…Supporting this notion, experiences of racial teasing and perceived racial discrimination are associated with racial minorities' internalization of general media standards of beauty (Cheng, 2014), and body dissatisfaction (Iyer & Haslam, 2003;Reddy & Crowther, 2007).…”
Section: Shifting Actuals and Idealsmentioning
confidence: 90%